Ergogenic effect of nitrate supplementation: A systematic review and meta-analysis - Senefeld, J. W.; Wiggins, C. C.; Regimbal, R. J.; Dominelli, P. B.; Baker, S. E.; Joyner, M. J. (Medicine & Science in Sports & Exercise, 2020)
Although over 100 studies and reviews have examined the ergogenic effects of dietary nitrate (NO3-) supplementation in young, healthy men and women, it is unclear if participant and environmental factors modulate the well-described ergogenic effects—particularly relevant factors include biological sex, aerobic fitness, and fraction of inspired oxygen (FiO2) during exercise. To address this limitation, the literature was systematically reviewed for randomized, crossover, placebo-controlled studies reporting exercise performance outcome metrics with NO3- supplementation in young, healthy adults. Of the 2033 articles identified, 80 were eligible for inclusion in the meta-analysis. Random-effects meta-analysis demonstrated that exercise performance improved with NO3- supplementation compared with placebo (d = 0.174; 95% confidence interval (CI), 0.120-0.229; P < 0.001). Subgroup analyses conducted on biological sex, aerobic fitness, and FiO2 demonstrated that the ergogenic effect of NO3- supplementation was as follows: 1) not observed in studies with only women (n = 6; d = 0.116; 95% CI, -0.126 to 0.358; P = 0.347), 2) not observed in well-trained endurance athletes (=65 mL·kg-1·min-1; n = 26; d = 0.021; 95% CI, -0.103 to 0.144; P = 0.745), and 3) not modulated by FiO2 (hypoxia vs normoxia). Together, the meta-analyses demonstrated a clear ergogenic effect of NO3- supplementation in recreationally active, young, healthy men across different exercise paradigms and NO3- supplementation parameters; however, the effect size of NO3- supplementation was objectively small (d = 0.174). NO3- supplementation has more limited utility as an ergogenic aid in participants with excellent aerobic fitness that have optimized other training parameters. Mechanistic research and studies incorporating a wide variety of subjects (e.g., women) are needed to advance the study of NO3- supplementation; however, additional descriptive studies of young, healthy men may have limited utility.